2016
DOI: 10.1074/jbc.m115.704015
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Active Guanylyl Cyclase B Requires Endoplasmic Reticulum-mediated Glycosylation, and Mutations That Inhibit This Process Cause Dwarfism

Abstract: C-type natriuretic peptide activation of guanylyl cyclase B (GC-B), also known as natriuretic peptide receptor B or NPR2, stimulates long bone growth, and missense mutations in GC-B cause dwarfism. Four such mutants (L658F, Y708C, R776W, and G959A) bound 125 I-C-type natriuretic peptide on the surface of cells but failed to synthesize cGMP in membrane GC assays. Immunofluorescence microscopy also indicated that the mutant receptors were on the cell surface. All mutant proteins were dephosphorylated and incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
(37 reference statements)
0
18
0
Order By: Relevance
“…The extracellular domain of GC-B is glycosylated and terminal N-linked glycosylation is required for the formation of an active GC catalytic domain [15, 16]. AMDM dwarfism-causing missense mutations are most often associated with receptors lacking terminal N-linked glycosylation that markedly reduces or abolishes the ability of GC-B to form an active catalytic domain [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular domain of GC-B is glycosylated and terminal N-linked glycosylation is required for the formation of an active GC catalytic domain [15, 16]. AMDM dwarfism-causing missense mutations are most often associated with receptors lacking terminal N-linked glycosylation that markedly reduces or abolishes the ability of GC-B to form an active catalytic domain [16].…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular domain of GC-B is glycosylated and terminal N-linked glycosylation is required for the formation of an active GC catalytic domain [15, 16]. AMDM dwarfism-causing missense mutations are most often associated with receptors lacking terminal N-linked glycosylation that markedly reduces or abolishes the ability of GC-B to form an active catalytic domain [16]. The intracellular portion of GC-B consists of a kinase homology domain that contains six chemically identified serine/threonine phosphorylation sites and one putative, functionally identified serine phosphorylation site [1719], a short coiled-coiled dimerization region, and a carboxyl-terminal GC domain [14, 20].…”
Section: Introductionmentioning
confidence: 99%
“…1, inset). Furthermore, each mutant was completely processed to a hormonally active terminally glycosylated and phosphorylated protein represented by the upper, most slowly migrating diffuse band when purified by SDS-PAGE (18). Guanylyl cyclase assays conducted under basal conditions (without NP) indicated that the basal enzymatic activity of each mutant was markedly elevated compared with basal activity of the WT enzyme (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The membrane was blocked with Odyssey LI-COR blocking buffer (Li-Cor Biosciences, Lincoln, NE) for 1 h at room temperature and then incubated overnight at 4°C with rabbit polyclonal antiserum #6327 against the C terminus of rat GC-B at a dilution of 1/10,000 in 1:1 blocking buffer/PBS with 0.1% Tween. The specificity of this antiserum for human and rat GC-B has been previously demonstrated (18,26,32,33). The membrane was washed 4 ϫ 5 min with TBST and then incubated with IRDye 680 goat anti-rabbit antibody (Li-Cor Biosciences) with a dilution of 1/10,000 for 1 h at room temp in 1:1 blocking buffer/PBS with 0.1% Tween and 0.01% SDS.…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 1 more Smart Citation